A STUDY ON MUTUAL FUNDS PERFORMANCE OFFERED BY BANKING COMPANIES IN INDIA - Vanshika Jindal (Innovative Research Thoughts, 2023)
The mutual fund industry in India has registered significant growth during the past decade or so, and has emerged as a significant financial intermediary. The growing importance of Indian mutual funds may be noted, in terms of the increased mobilization of funds and the increasing number of schemes and investors in the industry. To fulfill the expectations of millions of account holders, the mutual funds are required to function as successful institutional investors. We hope that attempt should highlight the efficiency and true competence of fund managers and augment the existing framework for identifying successful fund managers. It should benefit the investors, regulators, fund managers and other participants in the mutual fund industry in general. it is, generally, believed that professional fund managers have expertise in managing investments as they have access to information that is normally not available to common investors. In addition, they are supposed to possess superior analytical skills for making investment decisions. Thus, they are expected to provide a relatively higher rate of return on managed portfolios. However, higher returns per say may not indicate superior performance. The higher return may arise due to higher exposure to risk on investments, or may be attributed to luck or general market boom, rather than pure skill. This aspect is particularly worrying in case of India because of the less mature capital market conditions, wild fluctuations of the equity market, and lesser awareness among common investors..We try and adopt this idea throughout this study and try to look at various aspects of performance of equity mutual funds in India. With the current growing popularity of mutual funds particularly equity mutual funds in India, we think the study is appropriately timed. Mutual fund in Indian context is a challengeable phenomenon. It has attained commanding heights in the financial scenario of India. The main focus of this study is to compare the performance of SBI mutual fund scheme and ICICI prudential mutual fund scheme with the help of net asset value and the benchmark set by the association of mutual fund of India and to measure the risk and return associated with scheme and how they affect the performance of the scheme and to also study the capital invested in the current year.